Orientation-dependent tunneling electroresistance in Pt/Pb(Zr,Ti)O3/Nb:SrTiO3 ferroelectric tunnel junctions - Chunyan Ding; Chunyan Zheng; Weijie Zheng; Chenyu Dong; Yahui Yu; Zheng Wen (Journal of Advanced Dielectrics)
Orientation anisotropy is a well-known essential character for polarization characteristics of ferroelectric materials, which has been widely investigated in conventional ferroelectric random access memories. In this work, we study the effects of orientation on the tunneling electroresistance (TER) of ferroelectric tunnel junctions (FTJs). Rhombohedral Pb(Zr[Formula: see text],Ti[Formula: see text])O3 (PZT) that has the polar axis along the [Formula: see text] orientation is adopted as potential barriers and two kinds of FTJs that are composed of (001)- and (111)-oriented PZT barriers and Nb:SrTiO3 (Nb:STO) electrodes, respectively, are fabricated. The (111)-oriented Pt/PZT/Nb:STO FTJ exhibits a giant ON/OFF ratio of [Formula: see text], about 30 times that of the (001)-oriented device, due to the lowered PZT barrier in the ON state and the widen Schottky barrier in the OFF state based on current and capacitance analyses. In addition, compared to the (001)-oriented device, the (111)-oriented FTJ shows a sharper and faster switching between the ON and OFF states according to the nucleation-limited-switching dynamics model, giving rise to good linearity in memristive behaviors for synaptic plasticity and reliable retention and endurance properties for the resistance switching. The improved TER properties are ascribed to larger effective polarizations and 180∘ switching in the (111)-oriented PZT barrier. These results facilitate the design and fabrication of high-performance FTJ devices with the optimization of crystallographic orientation and polarization switching characteristics.